2017
DOI: 10.1002/jcp.26223
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the Nrf2/HO‐1/CO axis and therapeutic intervention with the CO‐releasing molecule CORM‐A1, in a murine model of autoimmune hepatitis

Abstract: Concanavalin A (ConA)-induced hepatitis is an experimental model of human autoimmune hepatitis induced in rodents by i.v. injection of Con A. The disease is characterized by increase in serum levels of transaminases and massive immune infiltration of the livers. Type 1, type 2, and type 17 cytokines play a pathogenic role in the development of ConA-induced hepatitis. To understand further the immunoregulatory mechanisms operating in the development and regulation of ConA-induced hepatitis, we have evaluated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 40 publications
1
35
0
Order By: Relevance
“…In addition, we also evaluated the transcriptomic analysis of MIF, DDT and their receptors in the brains of a mouse model of alcoholism. This analysis was carried out by DNA microarray analysis that represents a useful in silico toll for the better understanding of pathogenic pathways and the possible prediction of new diagnostic therapeutic approaches in several clinical settings, including immunoinflammatory and autoimmune diseases and fibrotic diseases (45,46,(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59). Our analysis first demonstrated that no differences in the expression of MIF, DDT and their receptors can be found in brains of both rodent models of AUD and patients with this condition.…”
Section: Discussionmentioning
confidence: 83%
“…In addition, we also evaluated the transcriptomic analysis of MIF, DDT and their receptors in the brains of a mouse model of alcoholism. This analysis was carried out by DNA microarray analysis that represents a useful in silico toll for the better understanding of pathogenic pathways and the possible prediction of new diagnostic therapeutic approaches in several clinical settings, including immunoinflammatory and autoimmune diseases and fibrotic diseases (45,46,(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59). Our analysis first demonstrated that no differences in the expression of MIF, DDT and their receptors can be found in brains of both rodent models of AUD and patients with this condition.…”
Section: Discussionmentioning
confidence: 83%
“…To this aim, gene expression signatures obtained from -omics data [28] are used to discover novel mechanisms of disease and searches inverse drug-disease relationships by matching gene expression profiles. We and others have used whole-genome expression databases for the better understanding of pathogenic pathways and the prediction of diagnostic and therapeutic strategies for a series of disorders-e.g., immunoinflammatory and autoimmune diseases [29][30][31][32][33][34][35][36][37], and cancer [38,39]-which has led to the identification of potential novel therapeutic targets [40][41][42][43][44][45][46][47][48][49][50][51]. However, gene perturbation alone cannot accurately predict treatment options due to variability related to disease genetics and epigenetics, as well as, experimental settings.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first meta-analysis to be performed exclusively on studies performed on a specific brain region from SCZ subjects and controls, rather than on studies encompassing different Brodmann areas or brain anatomical structures. The use of whole-genome expression databases has been largely exploited by our group and others [37][38][39][40][41] for the characterization of pathogenic pathways and to identify therapeutic targets for a variety of disorders, such as autoimmune diseases [42][43][44][45][46][47][48][49][50], cancer [44,51,52], and has allowed researchers to characterize pathogenic pathways [53][54][55][56], and potential therapeutic targets [57][58][59][60][61].…”
Section: Discussionmentioning
confidence: 99%